3D Modeling and Visual Simulation of Plain Knitted Structures - Li, Yinglin (International Journal of Online and Biomedical Engineering (iJOE), 2013)
Weft knitted fabrics are widely used in clothing textiles and technical applications, such as sweater and underwear, etc. The geometrical modeling of weft knitted structures is useful to predict fabrics properties and for creating physical models. How to realize the realistic computer simulation of plain knitted structures, much research is still needed. By measuring the loop structure size of fabrics produced by the circular machine and flat machine, a 3D geometrical model of plain loop with combination of empirical and theoretical was developed. The loop model has a total of 17 data points. Cubic NURBS curve was used to generate central path of yarn in plain loop. The circle was selected as the cross-section of yarn. In Visual C++ and OpenGL environment, then the 3D computer simulation of plain knitted fabric was realized. The simulation results distinctly show the intermeshed loops effects of knitted structures in 3D space.